527 Academic Medical Center Clinical Research Professional Recruitment, Retention and Diversity. (April 2022) - Jones, Carolynn Thomas; Kolb, Robert; Pullum, Cherese; Carter, Karen K; ,; Fitz-Gerald, Meredith; Marchant, Mark; Mendell, Angela; Knapke, Jacqueline; ,
Abstract : OBJECTIVES/GOALS: a) Explore topics related to AMC CRP job titles, descriptions, and pre-requisites for hire b) Describe impact of COVID-19 on the AMC CRP workforce c) Discuss opportunities for improving diversity in the CRP workforce d) Discuss opportunities to enhance institutional staffing culture to retain CRP workforce METHODS/STUDY POPULATION: Qualitative data from a series of workshop breakout sessions and open-text survey materials focusing on AMC CRP recruitment, retention and diversity were analyzed to inform content and recommendations for clinical research job titles and descriptions, pre-requisites, diversity, and current needs. RESULTS/ANTICIPATED RESULTS: While certain institutions have established competency-based frameworks for job descriptions and career ladders, standardization remains generally lacking across CTSA hubs. Significant hiring needs have reached exponential proportions across hubs, unable to meet current and projected clinical research goals. Data confirmed an urgent need for closing gaps in clinical research workforce at AMCs, especially for improving diversity and equity of personnel. Improved collaboration with human resource departments, engagement with principal investigators, and overcoming both organizational and resource challenges were suggested strategies, as well as pipeline development via outreach to universities, community colleges, and high schools to raise awareness of the professional pathways for CRPs. DISCUSSION/SIGNIFICANCE: Based on input from 130 CRP leaders at 38 CTSA hubs and 4 IDeA sites evaluating data from 23 breakout transcripts and 92 surveys from the Collaborative Conversations Unmeeting, new opportunities emerged during the analysis. The findings will be summarized in a 2022 Synergy manuscript including best practice benchmarking recommendations.